Radiation sterilization of Honey and Honey-Alginate Wound Dressing from Stingless Bee (Tetragonula biroi) Collected from Sta. Maria, Laguna, Philippines - Davison Torres Baldos; Joseph Mallari Puno; Levelyn Mitos Mesa Tolentino; Djowel Recto Villanueva Montefalcon; Gilberto Tura Diano; Celia Oprenario Asaad (Journal of Tropical Life Science, 2021)
This study was conducted to determine the effect of radiation sterilization on alginate wound dressing containing honey from the Philippine stingless bee, Tetragonula biroi. Our results show that a radiation dose of 30 kGy did not affect the antibacterial property of honey against Staphylococcus aureus. Electron-beam irradiation did not produce significant alterations in the physicochemical properties (pH, total soluble solids, and flavonoids); however, the total phenolics was significantly increased in honey with higher irradiation doses. Demonstrating that irradiation can be applied to honey with negligible physicochemical effects, honey was incorporated in alginate and exposed to a sterilization dose of 25 kGy using an electron beam facility.Â Irradiation did not affect the physicochemical properties (pH, moisture content, gel fraction, moisture vapor transmission rate (MVTR), and fluid handling capacity) of the honey alginate wound dressing (HAWD). The perspectives for the potential use of irradiated HAWD as a natural product-based substitute for commercial wound care products may be considered.